Ethics, human rights and HIV vaccine trials in low-income settings. Issue 5 (6th December 2011) - London, Leslie; Kagee, Ashraf; Moodley, Keymanthri; Swartz, Leslie
Abstract : The massive growth in global health research in past decades has posed many challenges for its effective ethical oversight, not least of which is how best to provide effective protection of research participants. The extent of the HIV epidemic in sub-Saharan Africa in particular makes research into prevention technologies for HIV, including HIV vaccine research, a global priority. However, the need for vaccine research must be considered in conjunction with the individual's right to informed consent, which is based on the principle of respect for autonomy. One of the primary human rights violations likely to occur in the context of HIV vaccine research is that potential research participants may not fully understand what participation in research studies entails. People who elect to enrol in HIV vaccine trials are required to understand both the potential negative effects of participation (eg, discrimination) as well as complex scientific concepts such as randomisation and prophylaxis in order to be ethically enrolled. In this study, two vignettes are presented to illustrate two core issues in conducting phase III HIV vaccine trials in low-income countries—namely, (1) from the perspective of participants, the extent to which understanding is a prerequisite for consenting to participate in a trial, and (2) from the perspective of trial investigators, whether it is appropriate to persuade eligible people to enrol in a trial, even though their initial reaction is to decline to participate. These vignettes are used to analyse these issues through the prisms of research ethics and human rights in order to identify helpful synergies. It is argued that the human rights perspective provides a helpful lens on ethical issues.